Secular trends in the prevalence of meeting 24-hour movement guidelines among U.S. adolescents: evidence from NHANES 2007–2016 - Liu, Xue-qing; Liu, Mei-ling; Wu, Zhuo-wen; Liang, Jing-hong (Frontiers in Public Health, 2024)
Background The 24-Hour Movement Guidelines (24-HMG) recommend a balanced combination of physical activity (PA), sedentary behavior (SB) and sleep (SLP) for optimal health. However, there is limited understanding of how well U.S. adolescents adhere to these guidelines. This study aims to analyze the prevalence trends of meeting the 24-HMG among a nationally representative sample of U.S. general adolescents. Methods The study included 2,273 adolescents (55.3% boys) aged 16–19 who participated in the National Health and Nutrition Examination Surveys (NHANES) from 2007 to 2016. The researchers categorized the adolescents based on whether they met various PA, SB, and SLP recommendations, as well as different combinations of these recommendations, separately for boys and girls. The prevalence rate, weighted by survey data, was calculated along with a 95% confidence interval (CI) to assess the changes in meeting the 24-HMG among U.S. adolescents across different survey years and sociodemographic subgroups. Results In the 2015–2016 cycle, approximately 6.3% of adolescents did not meet any of the three recommendations, while only 19.2% of adolescents achieved all three guidelines. Compliance with PA and SB recommendations among adolescents has decreased over time, from 72.5% (65.9% to 79.2%) to 64.2% (57.4% to 70.9%) for PA, and from 59.0% (49.6% to 68.4%) to 46.6% (37.8% to 55.5%) for SB, respectively, from 2007–2008 cycle to 2015–2016 cycle. Boys exhibited more favorable patterns in meeting different sets of recommendations compared to girls (p-value <0.001). This includes meeting both PA and SB guidelines (15.5% for boys and 11.1% for girls) and meeting both PA and SLP guidelines (19.5% for boys and 15.7% for girls). The level of parental education was found to have effect on meeting all three guidelines (Ptrend < 0.05). Conclusion We analyzed ten consecutive years of representative NHANES data to evaluate the prevalence meeting 24-HMG and found that the proportion of adolescents aged 16–19 in the U.S. who adhered to all three movement guidelines simultaneously has consistently remained low throughout each survey cycle. Notably, there has been a significant decline in the proportion of adolescents meeting the SB guideline.